Rapid Determination of the Monosaccharide Composition and Contents in Tea Polysaccharides from Yingshuang Green Tea by Pre-Column Derivatization HPLC - Yujie Ai; Zhi Yu; Yuqiong Chen; Xiaojing Zhu; Zeyi Ai; Shuyuan Liu; Dejiang Ni (Journal of Chemistry)
A pre-column derivatization high-performance liquid chromatography (HPLC) method was developed and optimized to characterize and quantify the monosaccharides present in tea polysaccharides (TPS) isolated from Yingshuang green tea. TPS sample was hydrolyzed with trifluoroacetic acid, subjected to pre-column derivatization using 1-phenyl-3-methyl-5-pyrazolone (PMP), and separated on an Agilent TC-C18 column (4.6 mm × 250 mm, 5 μm) with UV detection at 250 nm. A mixture of ten PMP derivatives of standard monosaccharides (mannose, ribose, rhamnose, glucuronic acid, galacturonic acid, glucose, xylose, galactose, arabinose, and fucose) could be baseline separated within 20 min. Moreover, quantitative analysis of the component monosaccharides in Yingshuang green tea TPS was achieved, indicating the TPS consisted of mannose, ribose, rhamnose, glucuronic acid, galacturonic acid, glucose, xylose, galactose, and arabinose in the molar contents of 0.72, 0.78, 0.89, 0.13, 0.15, 0.36, 0.39, 0.36, 0.36, and 0.38 μM, respectively. Recovery efficiency for component monosaccharides from TPS ranged from 93.6 to 102.4% with RSD values lower than 2.5%. In conclusion, pre-column derivatization HPLC provides a rapid, reproducible, accurate, and quantitative method for analysis of the monosaccharide composition and contents in TPS, which may help to further explore the relationship between TPS monosaccharides isolated from different tea varieties and their biological activity.